Development of Uniform Technique for Electromagnetic Compatibility Testing in Sony and External Facilities - Che Sarif, Muhamad Zulhayyie; Ahmad, Mohd Riduan; Abd. Aziz, Mohamad Zoinol Abidin (2024)
In today’s globalized world, the significance of Electromagnetic Compatibility (EMC) research has grown, particularly in establishing state-of-the-art EMC testing facilities. In Malaysia, SONY EMCS (Malaysia) Sdn Bhd (SONY) is one of the companies with such an EMC laboratory, supporting both Research and Development (R&D) and official certification processes. This paper presents parametric evaluation between SONY EMC testing laboratory and EMC testing laboratories in Taiwan and Indonesia with the objective to create a uniform, systematic, and sustainable EMC testing environment, not only within SONY but also in external labs. Several parameters and factors have been considered throughout the study, with the ultimate goal of designing a standardized approach for EMC correlation testing. Additionally, the project will develop a monitoring system to track and evaluate EMC lab performance, making measurements easier to monitor and assess. Each EMC test laboratory, whether in Malaysia, Indonesia, or Taiwan, exhibits varying performance, which can lead to discrepancies in product design when measured across different labs. As each EMC lab adheres to different standards, it is essential for labs to remain competitive to meet industry requirements and effectively compete with other testing facilities in the same region.